CircRNA_ACAP2 Suppresses EMT in Head and Neck Squamous Cell Carcinoma by Targeting the miR-21-5p/STAT3 Signaling Axis - Ma, Chuan; Shi, Tingting; Qu, Zhuli; Zhang, Aobo; Wu, Zuping; Zhao, Huaqiang; Zhao, Haoming; Chen, Hongyu (Frontiers in Oncology, 2020)
Circular RNAs (circRNAs) contain microRNA (miRNA)-specific binding sites and can function as miRNA sponges to regulate gene expression by suppressing the inhibitory effect of miRNAs on their target genes. MiR-21-5p has been reported to be involved in the development of head and neck squamous cell carcinoma (HNSCC) and plays an important role in the activation of epithelial-mesenchymal transition (EMT). However, the upstream regulatory mechanism and downstream targets of miR-21-5p in tumor cells remain unknown. CircRNA_ACAP2 inhibits the function of miR-21-5p by binding to its specific binding sites in HNSCC cells. Overexpression of CircRNA_ACAP2 inhibits the proliferation and migration of HNSCC cells, while downregulation of CircRNA_ACAP2 has the opposite effect. STAT3 is a direct target gene of miR-21-5p and a transcription factor of ZEB1. We demonstrate that CircRNA_ACAP2 functions as a tumor suppressor gene in HNSCC and that its function is regulated via the miR-21-5p/STAT3 signaling axis.